Measuring Corruption : Myths and Realities - Kaufmann, Daniel; Kraay, Aart; Mastruzzi, Massimo (World Bank, Washington, DC, 2012)
The report points out that over the past decade measuring corruption has become an ever-growing empirical field. This empirical analysis questions the traditional notion of viewing the firm as an 'investment climate taker' and thus ignoring the view that powerful conglomerates can also shape the business climate and thus become 'investment climate makers'. The study implies that it is warranted to move away from simply blaming government officials for prevailing corruption, and to question the value of popular initiatives such as voluntary-and often un-monitorable-codes of conduct. In this report, some popular notions are espoused, which either lack clarity or are not backed up by rigorous analysis or evidence. In this article the authors highlight some of the main issues in these debates, in the form of seven myths and their associated realities, and conclude by also pointing to some brief implications for the private sector role in fighting corruption.